Publisher Correction: 78,000-year-old record of Middle and Later Stone Age innovation in an East African tropical forest - Ceri Shipton (Nature Portfolio, 2018)
The originally published version of this Article contained an error in Fig. 3, whereby an additional unrelated graph was overlaid on top of the magnetic susceptibility plot. Furthermore, the Article title contained an error in the capitalisation of ‘Stone Age’. Both of these errors have now been corrected in both the PDF and HTML versions of the Article.